Oxytetracycline effects in specific biochemical pathways of detoxification, neurotransmission and energy production in Oncorhynchus mykiss - Rodrigues, S. (2022)
Oxytetracycline (OTC) is a tetracycline antibiotic, widely used in human and veterinary medicines, including in aquaculture. Given this use, OTC has been detected in different aquatic environments. Some recent works have demonstrated unintentional biological activity of OTC in non-target aquatic organisms. This study investigated the acute and chronic effects of OTC on the physiology of the fish species Oncorhynchus mykiss (rainbow trout), namely through the quantification of the activity of enzymes involved in different biochemical pathways, such as detoxification (phase II - glutathione S-transferases - GSTs, uridine-diphosphate-glucuronosyltransferases - UGTs), neurotransmission (acetylcholinesterase - AChE) and energy production (lactate dehydrogenase - LDH). The here-obtained data demonstrated the induction of GSTs activity in gills, and inhibition of AChE activity in eyes tissue, in chronically exposed organisms, as well as alterations in LDH activity following both exposures. Considering this set of results, we can infer that OTC exposure may have induced the glutathione pathway of detoxification in gills with the involvement of GSTs, or indirectly due to the metabolites that may have been produced. In turn, these metabolites may have interfered with the mechanism of neurotransmission, also causing physiological and biochemical disturbances in rainbow trout after OTC exposure, namely disturbances in energetic metabolism. In addition, it is important to stress that such occurrences took place at low, environmentally realistic levels of OTC, suggesting that organisms exposed in the wild may be putative targets of toxic effects by commonly used drugs such as antibiotics.